Ideas about art - Desmond, Kathleen Kadon (John Wiley & Sons, 2011)
"Ideas About Art is an intelligent, accessible introductory text for students interested in learning how to think about aesthetics. It uses stories drawn from the experiences of individuals involved in the arts as a means of exposing readers to the philosophies, theories, and arguments that shape and drive visual art. An accessible, story-driven introduction to aesthetic theory and philosophy Prompts readers to develop independent ideas about aesthetics; this is a guide on how to think, not what to think Includes discussions of non-western, contemporary, and discipline-specific theories Examines a range of art-based dilemmas across a wide variety of disciplines - from art and design and law to visual and museum studies"--Provided by publisher.